Sukses Belajar Bahasa Inggris Melalui Media Komputer - Sabriandi Erdian (Politeknik Negeri Padang, 2014)
The English language in the computer gives purpose very distinctive so that users indirectly been able to addthe vocabulary in English. The progress of technology and information century now it makes us as users of technologyshould be more enterprising and deft to selection because of a product produced is a picture with innovation,modification and information English as the deepening speak English .The process of learning and learning through the computer is a means to improve the English language.